The role of personality traits in pension decisions: findings and policy recommendations. Issue 27 (9th June 2019) - Balasuriya, Jiayi; Yang, Yu
ABSTRACT: Many countries need to stimulate pension participation and contribution to ensure their citizens are prepared adequately for retirement. Identifying at-risk groups with tendencies of not joining pension plans will help governments target strategies to improve pension awareness and participation. This study investigates the role of personality traits in pension decision making using data from the UK Household Longitudinal Study. Our results demonstrate that Extraversion significantly correlates with non-participation in private pensions, including both employer run and personal pensions. Individuals who are high in Conscientiousness are more likely to participate and pay more into personal pensions. Openness to experience is negatively correlated with saving via personal pensions. Agreeableness and Extraversion correlate inversely with the amount contributed to personal plans. This paper discusses our findings in detail and offers policy implications which may help promote pension participation and ease the problem of old age poverty.